Effect of Disintegrating Agents on Red Ginger (Zingiber officinale Roxb) Dry Extract Fast Disintegrating Tablets Using Direct Compression Method - RAHMAWATI, TIAS EKA (Media Farmasi Indonesia, 2024)
Red ginger (Zingiber officinale Roxb) is one of the medicinal plants that is effective as a medicine for nausea and vomiting. One of the techniques for developing traditional medicinal products is to make fast disintegrating tablets (FDT). This research aims to compare the effect of these various disintegrating materials on the physical properties of FDT. FDT red ginger extract is made using the direct compression method. The tablets obtained were physically evaluated including weight uniformity, hardness, friability, and disintegration time. The statistical results using the one-way ANOVA test show that between tablet formulas there are significant differences in tablet disintegration time with differences in the type of disintegrating agent. The data obtained shows that all formulas meet the physical properties test requirements for tablets. The tablet formula using crospovidone produces tablets with high hardness, low friability, and fast disintegration time